2003
DOI: 10.1038/nm903
|View full text |Cite
|
Sign up to set email alerts
|

Uncoupling protein-2 prevents neuronal death and diminishes brain dysfunction after stroke and brain trauma

Abstract: Whereas uncoupling protein 1 (UCP-1) is clearly involved in thermogenesis, the role of UCP-2 is less clear. Using hybridization, cloning techniques and cDNA array analysis to identify inducible neuroprotective genes, we found that neuronal survival correlates with increased expression of Ucp2. In mice overexpressing human UCP-2, brain damage was diminished after experimental stroke and traumatic brain injury, and neurological recovery was enhanced. In cultured cortical neurons, UCP-2 reduced cell death and inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

28
394
0
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 470 publications
(424 citation statements)
references
References 48 publications
28
394
0
2
Order By: Relevance
“…A possible causal relationship between redox status and cytokine production has been previously suggested in that increased basal GSH levels and SOD activity may result from high NGF levels (Guegan et al, 1998(Guegan et al, , 1999de Bilbao et al, 2004;Arsenijevic et al, 2006). Consistent with their possible role in neuroprotection (Guegan et al, 1999;Mattiasson et al, 2003), the differences in GSH, UCP2 mRNA and NGF levels persisted between infected and non-infected mice after MCAO. In the absence of a specific antibody for brain UCP2, it was not possible to assess the impact of UCP2 mRNA changes on protein levels.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…A possible causal relationship between redox status and cytokine production has been previously suggested in that increased basal GSH levels and SOD activity may result from high NGF levels (Guegan et al, 1998(Guegan et al, , 1999de Bilbao et al, 2004;Arsenijevic et al, 2006). Consistent with their possible role in neuroprotection (Guegan et al, 1999;Mattiasson et al, 2003), the differences in GSH, UCP2 mRNA and NGF levels persisted between infected and non-infected mice after MCAO. In the absence of a specific antibody for brain UCP2, it was not possible to assess the impact of UCP2 mRNA changes on protein levels.…”
Section: Discussionmentioning
confidence: 56%
“…In the absence of a specific antibody for brain UCP2, it was not possible to assess the impact of UCP2 mRNA changes on protein levels. However, previous data using UCP2 transgenic and UCP2 KO mice have shown that UCP2 plays a central role in brain neuroprotection following ischemia (Mattiasson et al, 2003;de Bilbao et al, 2004). …”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Altered AMPA receptor subunit expression is debated as a factor in ischemic preconditioning (Sommer and Kiessling, 2002;Tanaka et al, 2002;Yamaguchi et al, 1999), but some evidence indicates that, in apparent contrast to the gerbil, preconditioning in the rat may increase expression of the Ca 2 þ impermeable, rapidly desensitizing GluR2 subunit (Alsbo et al, 2001;Kjøller and Diemer, 2000). Recent results have associated increased expression of uncoupling protein-2 (UCP-2) with neuroprotection (Diano et al, 2003;Mattiasson et al, 2003), but its potential impact on ischemic depolarization per se is unclear. Established global ischemia models are characterized by very low residual flow during occlusion (Kågströ m et al, 1983;Pulsinelli et al, 1982), but perfusion effects of preconditioning are also possible.…”
Section: Changes In Depolarization Kinetics Associated With Preconditmentioning
confidence: 99%
“…As mitochondrial ROS production is dependent on the mitochondrial potential, mild uncoupling could effectively decrease ROS generation. Therefore, UCP2 activation by ROS could be considered as a protective feed-back loop, as suggested by studies in neurons or cardiomyocytes [22,23].…”
Section: Introductionmentioning
confidence: 99%